Increasing the Brand Awareness of Sahabat Christian School through A Website - Irene Juliana Hia (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Sahabat Christian School Batam was established in 2011. This school provides 2 programs which are Kindergarten program and Elementary programs. Sahabat Christian School Batam also has 2 competitors, which are Holy Vision School (Visi Kudus) and Eben Haezer school. They were considered as competitors because of the price, location, and service. The main problem of Sahabat Christian School is low brand awareness. In other words there are only a few people who know about the existence of this school and some people know about this school but they do not really know what services that this school offers. In order to solve this problem, Sahabat Christian School needs a tool which can highlight their Uniques Selling Point to give credible and trustworthy information about this school. This tool is a website. As the main purpose is to increase brand awareness, a website will be the best solution since a website can help to highlight the Uniqueness and provides school’s information in detail and trustworthy. There are 3 highlighted USP’s: Christian Academic, Christian values, and non-academic. By highlighting their USP could increase the school brand awareness and persuade them to use the school’s services.Keyword: Promotional Tool, Brand Awareness, Unique Selling Point, Website